(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Studies were carried out on the preparation of oleo-resinous wood varnishes by utilizing safflower (Carthamus tinctorius) seed oil. It was observed that safflower seed grown under the soil-texture and climatic condition of Bangladesh, contains about 32 % golden yellow coloured drying oil. The physico-chemical characteristics of the oil were determined by the conventional methods and the fatty acid compositions by GLC. From the results it is evident that the oil can be used suitably in paint and varnishes on account of its high linoleic acid content (75 %) and higher iodine value (148). The oleoresinous wood varnishes was prepared by utilizing safflower seed oil in an open stainless steel beaker by heating the oil with rosin and glycerol. The cooking temperature was maintained at 300O C for ½ an hour. Zinc oxide and lead oxide were used as mould growth inhibitor and catalyst respectively. The varnish thus prepared was found to be water resistant and can be applied on wood surface as tack free coating. Bangladesh J. Sci. Ind. Res. 41(1-2), 77-82, 2006